Augmented Reality-based Mathematics Worksheet for Online Learning During Covid-19 Pandemic - S, Soma Salim; Darmawan, Fitrah A.; Jainuddin, Jainuddin (Universitas Negeri Makassar, 2020)
Abstract. The aim of this study is to create and develop an augmented reality-based mathematics worksheet that can be used for online learning during covid-19 pandemic. The application created has been tested using three out of eight characteristics of ISO 25010 quality standards, which are functional suitability, compatibility, and usability. The results show that the augmented reality-based mathematics worksheet has a very high quality. Further explanations regarding the application and its implications are discussed.